QUEEN ELIZABETH II'S ANXIETY IN STHEPEN FREARS' THE QUEEN MOVIE (2006): A PSYCHOANALYTIC APPROACH - Setiawan, Agus (2011)
The study tries to explore major Character's anxiety. The objective of the study is to analyze the major character based on the structural elements of the movie and psychoanalytic perspective. The researcher applies the theory of psychoanalytic proposed by Sigmund Freud. The writer conducts the research by using qualitative method that uses the library research, while the data sources are literary data that are divided into two categories, primary and secondary data. The primary data are the movie subtitle The Queen itself and the secondary data include several references books of Psychoanalysis. The object of the research is the movie entitled The Queen directed by Stephen Frears. The results of the study are as follows. Firstly, the structural elements of the movie present a unity. It appears in the beginning, the middle, and the end of the story. Secondly, the psychoanalytic analysis shows that the problem of major characters encounters and causes the conflict between id, ego, and superego. Then, it develops to become anxiety and influences Queen Elizabeth II's mental condition.